Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Luiten CA; Hinkley SFR; Roskruge NR; Semese SA; Heath A-LM; Perry TL; Rehrer NJ; Sims IM (Elsevier B.V., 2026)
Taewa are varieties of potato introduced to New Zealand by European explorers in the late 18th century. The aim of this research was to extract and characterise cell wall polysaccharides from three varieties of taewa (Huakaroro, Tutaekuri, Moemoe) and compare their composition and structure with a modern potato variety (Agria). The yield of cell walls ranged from 22.8 mg to 42 mg per gram fresh weight potato and was higher for Tutaekuri than other taewa varieties and Agria. Cell walls of Tutaekuri also contained the highest amounts of galactose and the highest level of pectic polysaccharides compared with other varieties. Sequential fractionation of the cell walls gave two pectic polysaccharides fractions (imidazole + Na2CO3 and residue wash), and a hemicellulose fraction (4 M KOH). The residue wash fractions contained higher proportions of rhamnogalacturonan-I than the imidazole + Na2CO3 fraction. Constituent sugar and glycosyl linkage compositions indicated that there were differences in the detailed structural features of the pectic polysaccharides among the taewa varieties and Agria. The imidazole + Na2CO3 fraction from Moemoe had a lower rhamnogalacturonan-I/homogalacturonan ratio and a lower side-chain/rhamnose ratio than the other varieties. Glycosyl linkage analysis indicated that Moemoe had shorter galactan side-chains than the other varieties. Constituent sugar and glycosyl linkage analysis of the 4 M KOH fractions gave linkages that were typical of solanaceous xyloglucans. This knowledge provides added value to taewa suggesting that as well as their important role as a taonga species for Māori, they could contribute to human health outcomes.
Keywords: Taewa (Māori potato); Solanum tuberosum; Cell wall polysaccharides; Sequential extraction; Methylation analysis